2017
DOI: 10.18632/oncotarget.17434
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 regulates the JNK signaling pathway and increases apoptosis in hepatocellular carcinoma

Abstract: Notch1-induced pathways are involved in cell growth, apoptosis, motility, and invasion in many cancers. In the present study, the expression of Notch1 and NICD1 was detected in hepatocellular carcinoma (HCC) tissues using in-vitro assays. And then, we explored cell biology and signaling pathways using Notch1 siRNA or plasmids. Here, the expression of Notch1 and NICD1 was significantly decreased in HCC tissues. In-vitro, Notch1 plasmids inhibited cell proliferation, migration and invasion, but enhanced apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…CXCR4 is a transmembrane G-coupled receptor acting via binding to its CXC motif ligand 12 (CXCL12) (Hajinejad et al, 2017;Khanlarkhani et al, 2017;Omidi et al, 2015Omidi et al, , 2017. Notch1 increases apoptosis in HCC cells via activation JNK (Sui et al, 2017). However, evidence for possible implication of melatonin on these signaling pathways for HCC is too poor.…”
Section: Other Signaling Pathwaysmentioning
confidence: 99%
“…CXCR4 is a transmembrane G-coupled receptor acting via binding to its CXC motif ligand 12 (CXCL12) (Hajinejad et al, 2017;Khanlarkhani et al, 2017;Omidi et al, 2015Omidi et al, , 2017. Notch1 increases apoptosis in HCC cells via activation JNK (Sui et al, 2017). However, evidence for possible implication of melatonin on these signaling pathways for HCC is too poor.…”
Section: Other Signaling Pathwaysmentioning
confidence: 99%
“…Another circRNA, hsa_circ_0005986, was also down-regulated in HCC tissues and HCC cell lines, and its lower expression was correlated with chronic hepatitis B family history, tumor diameters, microvascular invasion and Barcelona Clinic Liver Cancer (BCLC) stage 27 . Further studies demonstrated that knocking down of hsa_circ_0005986 increased miR-129-5p levels, leading to reduced expression of its target gene Notch homolog 1(NOTCH1), a receptor which plays an important role in HCC carcinogenesis and metastasis 27 , 51 - 54 . However, knocking down of miR-129-5p significantly promoted, while over-expression of this miRNA greatly inhibited, the expression of hsa_circ_0005986 and NOTCH1 27 .…”
Section: Down-regulated Circrnas In Hccmentioning
confidence: 99%
“…The activation of NOTCH1 has been widely shown to be correlated with mammary tumorigenesis in animal models, and the upregulation of Notch receptors has been frequently observed in many cancer types. Furthermore, NOTCH1 has been shown to promote metastasis in many cancer types, including RCC, liver cancer, head and neck cancer, and gastric cancer [26][27][28][29]. It correlated with the formation of vasculogenic mimicry (VM) and the expression of epithelial-to-mesenchymal transition (EMT) biomarkers to be involved in the process of tumor metastasis [30,31].…”
Section: Discussionmentioning
confidence: 99%